Silent Harm: evidence-informed training for stakeholders working in interpreter-mediated gender-based violence settings - Leeson, Lorraine (My University, 2025)
Discussion and disclosure of domestic, sexual and gender-based violence (DSGBV) remains taboo for many. DSGBV was spotlighted as a ‘shadow pandemic’ across the Covid-19 pandemic with significant increases in instances of abuse recorded across the period. Concurrently, lack of access to any information around DSGBV in non-dominant languages including signed languages, along with limited organised opportunities to discuss DSGBV has left many speakers/signers experiencing DSGBV in a vacuum (Napier, Clark, Leeson, & Quigley, 2024; Opsahl & Pick, 2017). There is robust consensus that migrants, refugees and members of deaf communities who experience DSGBV should have timely access to interpretation by competent and specially trained professionals in a respectful framework of practice based upon integrity, which upholds their human rights. This, in turn, facilitates equitable engagement with the legal system and relevant support services (e.g. Admire & Ramirez, 2021). The literature also reveals a need for further research on interpreter preparedness towards enhanced understanding of its impact on DSGBV disclosures. Vicarious trauma for interpreters and gaps in understanding amongst law enforcement and support agencies about what constitutes positive interpreting experiences for all parties, are among the areas most urgently requiring further research. We tackled these challenges with the multidisciplinary Justisigns 2 project team (2020-23), developing evidence-informed resources for key stakeholders who engage with deaf, refugee, and migrant women and girls who experience GBV and use a language other than that of their host community. Follow on work (Royal Society of Edinburgh/ Royal Irish Academy) facilitated roll-out with police, interpreters and other stakeholders in rural Scotland and Ireland. Significant work with deaf women across the project raised consciousness around DSGBV and led to the co-creation of glossaries of DSGBV terms in Irish Sign Language (ISL) and British Sign Language (BSL). In this paper, we present results of a survey of key stakeholders from Ireland, the UK and Spain and outline our development of specialist training. We discuss how legislative frameworks and national policies around DSGBV and equality need further co-enmeshment, and we consider how minority community women who do not speak the host language, can be better included in informing and guiding development of processes that impact them.
Proceedings of the 8th International Conference on Gender Research
8th International Conference on Gender Research
PUBLISHED
https://doi.org/10.34190/icgr.8.1.3296
Porto, Portugal
Keywords: domestic, sexual and gender-based violence (DSGBV), interpreting services, deaf and migrant women, sign languages, language concordant services; Inclusive Society; Asylum Seekers & Refugees; British Sign Language; Deaf Studies; IMMIGRANTS; Irish Sign Language; Rape/Sexual Abuse; Spanish Sign Language; TRANSDISCIPLINARITY; gender based violence; interpreting studies; intersectional research; sign language interpreter education; sign language interpreting